KERAPATAN LONTAR (Borassus flabellifer L.) DI HUTAN PANTAI DESA TABANIO, KALIMANTAN SELATAN - Hery Fajeriadi; Dharmono Dharmono; Muhammad Rizki Anwar (Universitas Lambung Mangkurat, 2019)
Coastal areas gather various forms of ecosystems, including coastal forests adjacent to coastal eulitoral zones, swamp water bodies, rivers, and estuaries. The coastal forest of Tabanio Village is a traditional area that has been guarded for generations, in which various types of stands grow, including lontar plants. But the documentation of lontar plants has not been done, while the coastal area began to be developed into tourist attractions. This study aims to document the density of lontar plants in the coastal forests of Tabanio Village, as supporting ecotourism data. Data were collected with a total roaming, with an area size of 800 m x 2,500 m. Data collected are morphology and number of individuals. Morphological analysis is done descriptively, while density analysis is done descriptively quantitative, and is associated with environmental factors. Lontar plants were found with a total of 27 individuals, and the density value is 0.135 per hectare. The main limiting factor for the lack of lontar populations in the region is the high soil moisture compared to previous studies in different places.